2021
DOI: 10.1021/acs.jproteome.1c00374
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Serum Lipidomics for Detecting Incipient Dementia in Parkinson’s Disease

Abstract: While a number of methods are available for analyzing lipids, unbiased untargeted lipidomics with high coverage remains a challenge. In this work, we report a study of isotopestandard-assisted liquid chromatography mass spectrometry lipidomics of serum for biomarker discovery. We focus on Parkinson's disease (PD), a neurodegenerative disorder that often progresses to dementia. Currently, the diagnosis of PD is purely clinical and there is limited ability to predict which PD patients will transition to dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
(132 reference statements)
1
13
0
Order By: Relevance
“…The obtained intensity ratios were filtered by relative standard deviation (RSD) of quality control experimental replicates (RSD ≤30%). Noninformative features (i.e., internal standards and features with near‐constant values between the groups determined by low RSD) were also removed before auto‐scaling, normalization to the median value and statistical analysis employing MetaboAnalyst 5.0 (Zardini Buzatto et al., 2021; Zardini Buzatto et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The obtained intensity ratios were filtered by relative standard deviation (RSD) of quality control experimental replicates (RSD ≤30%). Noninformative features (i.e., internal standards and features with near‐constant values between the groups determined by low RSD) were also removed before auto‐scaling, normalization to the median value and statistical analysis employing MetaboAnalyst 5.0 (Zardini Buzatto et al., 2021; Zardini Buzatto et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…CSH (charged surface hybrid) particles were designed to enable sample loading and improve peak symmetry when using low ionic strength mobile phases, as instructed by the manufacturer. Reversed-phase columns, such as the chosen CSH C18, are broadly used for metabolomics investigation in different matrices such as plasma [ 20 ], serum [ 28 ], urine [ 29 ], tissue [ 30 ], and cell cultures [ 31 ], as chromatographic columns of this type generally result in the detection of more features [ 32 ]. The ERM obtained after the co-cultivation of both cell types was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, untargeted lipidome assessments were utilized to detect incipient dementia in PD. Lipidome analysis by isotope-standard-assisted liquid chromatography of PD patients’ serum revealed that an association with patients transitioning to the development of dementia could be characterized by a 5-lipid biomarker panel [ 97 ].…”
Section: Lipids and Parkinson’s Diseasementioning
confidence: 99%